Hospitalizations for childhood cancer in the north of Minas Gerais state, Brazil, between 2008 and 2015 based on the DATASUS - Araújo Lima, Paula; Rodrigues de Queiroz, Wanessa; Cardoso Rocha, Fernanda; Barbosa Cruz, Isabela; Lúcia Câmara Dias, Jannayne; Ribeiro de Andrade Neto, Gregório; Nunes Ferreira, Tadeu (Revista Unimontes Científica, 2020)
Objective: To describe the hospitalizations due to childhood cancer in the North of Minas Gerais state, Brazil, from 2008 to 2015, based on data from the Department of Informatics of the Unified Health System (DATASUS). Method: This is a descriptive epidemiological study, with data collected from DATASUS, accessed in March/April 2016. The collected data were all cases of hospitalizations for cancer/leukemia in children under 14 years in the northern region of Minas Gerais, from 2008 to 2015. Since DATASUS is a public domain databank, this work did not have to be submitted to the Committee on Ethics in Research. Results: There were 2,020 cancer hospitalizations of children from 0 to 14 years old in the North of Minas Gerais state, regardless of the type of neoplasm and gender. Among them 1,916 took place in the municipality of Montes Claros, which accounted for 94.8% of the total, with 54% (1,094) males and 46% (926) females. In terms of the nature of attendance, 86.4% of the total was represented by urgent attendances, while elective ones amounted to 13.6%. Public healthcare attendances accounted for 5.4% of the total. This varied according to the healthcare system, since the reference institutions also provide services by the SUS, either being private or philanthropic. Conclusion: This study might assist health managers in decision-making when dealing with issues related to the number of beds available for this type of patients. It might also contribute to the development and elaboration of hypotheses, based on epidemiological studies that might be used by hospital institutions referenced for child oncological treatment, therefore providing a better healthcare assistance.